2021
DOI: 10.3390/md19100549
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Compounds from Microalgae: A Review

Abstract: The demand for natural products isolated from microalgae has increased over the last decade and has drawn the attention from the food, cosmetic and nutraceutical industries. Among these natural products, the demand for natural antioxidants as an alternative to synthetic antioxidants has increased. In addition, microalgae combine several advantages for the development of biotechnological applications: high biodiversity, photosynthetic yield, growth, productivity and a metabolic plasticity that can be orientated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 135 publications
(198 reference statements)
0
81
0
1
Order By: Relevance
“…Carotenoids are high-value pigments produced by photosynthetic organisms with several benefits in terms of health and nutrition. These molecules are important antioxidants, and their applications range from animal feed to human food and dietary supplements, cosmetics and pharmaceuticals [ 1 , 2 , 3 ]. The global carotenoid market is expected to have a steady increase of 5% during the next decade, with carotenoid sales likely to be over 2 billion US Dollars by 2031 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids are high-value pigments produced by photosynthetic organisms with several benefits in terms of health and nutrition. These molecules are important antioxidants, and their applications range from animal feed to human food and dietary supplements, cosmetics and pharmaceuticals [ 1 , 2 , 3 ]. The global carotenoid market is expected to have a steady increase of 5% during the next decade, with carotenoid sales likely to be over 2 billion US Dollars by 2031 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studied species gave IC50 values close to the reference butylated hydroxytoluene. Coulombier et al (2021), according to the data about the table in the review article that which they evaluated many studies on the antioxidant compounds of microalgae, they reported the IC50 value of Chlorella vulgaris and Chlamydomonas reinhardtii species as 55-73 µg mL -1 , and the IC50 value of ascorbic acid, which was determined as positive control, as 127.5 µg mL -1 . Also, according to the author, the antioxidant activity of the Chlorella genus has been proven by several researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds belonging to mycosporin-like amino acids occur in a wide variety of marine organisms including algae. Their main function is protection from UV, but some of them have antioxidant properties (Coulombier et al 2021 ).…”
Section: Cellular Antioxidantsmentioning
confidence: 99%